Developing Speaking Activity Model through Set Phrases for Secondary Students - Alvi Nurhidayati; Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2018)
The present study is aimed to describe the development of a model of teaching speaking called Set Phrases, to reveal the strengths and limitations of the model, and to reveal students’ perception on the implementation of Set Phrases in SMP Negeri 1 Candimulyo Magelang. This study belongs to an Educational Research and Development. The model was developed by adapting Borg and Gall’s model (1983) simplified into six steps: 1) Research and Information Collecting or Need Analysis, 2) Planning, 3) Develop Preliminary Product, 4) Field Testing and Experts’ Judgments, 5) Product Revision, 6) Dissemination and Implementation. The field try-out was conducted in one class of grade VII students of SMP Negeri 1 Candimulyo Magelang. The data were collected from interview, questionnaire, teacher’s field notes, students’ note, test results, and experts’ feedback. The collected data were analyzed using four stages of Miles and Huberman (1994) qualitative data analysis: data collection, data reduction, data displayed, and drawing and verifying conclusion. The result of the research showed that Set Phrases was an effective model to enhance students’ speaking skill indicated by the increasing students’ fluency, accuracy, and self-confidence in speaking. Set Phrases indicates to be appropriate for novice learners in large classes and for those who have low motivation in learning English. Besides, the students got benefits of understanding English materials more easily, increasing motivation, and having better interaction with others. Furthermore, this Set Phrases is an effective model to conduct speaking in classroom activities because it emphasizes on continuously graded materials.